The fish fauna of Anambra river basin, Nigeria: species abundance and morphometry - Ejikeme Odo, Gregory (2009)
The fish yields of most Nigeria inland waters are generally on the decline for causes that may range from inadequate management of the fisheries to degradation of the water bodies. Sustainable exploitation requires knowledge of the ichthyofaunal composition in the water bodies. We did a survey of fish species in Anambra river basin for 22 months. Fish samples were collected using four different gears –hook and line of size 13, caste nets, gill nets, and cages of mesh sizes of 50mm, 75mm, and 100mm each. We recorded 52 fish species belonging to 17 families: 171, 236, and 169 individuals at Ogurugu, Otuocha, and Nsugbe stations respectively. Two families, Characidae, 19.5 %, and Mochokidae, 11.8%, constituted the dominant fish families in the river. The dominant fish species were Citherinus citherius, 9.02%, and Alestes nurse, 7.1%. Other fish species with significant abundance were Synodontis clarias 6.9%, Macrolepidotus curvier 5.7%, Labeo coubie 5.4%, Distichodus rostrtus 4.9%, and Schilbe mystus 4.5%. The meristic features of the two most abundant fish species caught are as follows: Citharinus citharius dorsal fins 20, anal fins 30, caudal fins 21, pectoral fins, 9 and 8 ventral fins, and Alestes nurse 10 dorsal fins, 14 anal fins, 31 caudal fins, 7 pectoral fins and 6 ventral fins. The morphometric features of the two most abundant fish species are Citharinus citharius total length 300mm, standard length 231mm, head length 69mm, body length 101mm, body girth 176 mm, body weight 900mg. Alestes nurse total length 200, standard length 140mm, head length 60mm, body length 80mm, body girth120mm, body weight 400mg. The most abundant animal utilizing the basin was Ardea cinerea(D3) with 22.2% occurrence (D4) and this was followed by Caprini with 13.51%, and Varanus niloticus, 10.04%. The least abundant animals utilizing basin were Chephalophus rufilatus, and Erythrocebus patas, with 0.58% each of occurrence